Attenuation of HECT-E3 ligase expression rescued memory deficits in 3xTg-AD mice - Suresh, Pavithra; Jasmin, Sureka; Yen, Yun; Hsu, Hao-Jen; Varinthra, Peeraporn; Pairojana, Tanita; Chen, Chien-Chang; Liu, Ingrid Y. (Frontiers in Aging Neuroscience, 2022)
Alzheimer's disease (AD) is one of the most common progressive neurodegenerative disorders that cause deterioration of cognitive functions. Recent studies suggested that the accumulation of inflammatory molecules and impaired protein degradation mechanisms might both play a critical role in the progression of AD. Autophagy is a major protein degradation pathway that can be controlled by several HECT-E3 ligases, which then regulates the expression of inflammatory molecules. E3 ubiquitin ligases are known to be upregulated in several neurodegenerative diseases. Here, we studied the expressional change of HECT-E3 ligase using M01 on autophagy and inflammasome pathways in the context of AD pathogenesis. Our results demonstrated that the M01 treatment reversed the working memory deficits in 3xTg-AD mice when examined with the T-maze and reversal learning with the Morris water maze. Additionally, the electrophysiology recordings indicated that M01 treatment enhanced the long-term potentiation in the hippocampus of 3xTg-AD mice. Together with the improved memory performance, the expression levels of the NLRP3 inflammasome protein were decreased. On the other hand, autophagy-related molecules were increased in the hippocampus of 3xTg-AD mice. Furthermore, the protein docking analysis indicated that the binding affinity of M01 to the WWP1 and NEDD4 E3 ligases was the highest among the HECT family members. The western blot analysis also confirmed the decreased expression level of NEDD4 protein in the M01-treated 3xTg-AD mice. Overall, our results demonstrate that the modulation of HECT-E3 ligase expression level can be used as a strategy to treat early memory deficits in AD by decreasing NLRP3 inflammasome molecules and increasing the autophagy pathway.